Systematic review of Marburg virus vaccine nonhuman primate studies and human clinical trials. Issue 2 (8th January 2021) - Dulin, Nicholas; Spanier, Adam; Merino, Kristen; Hutter, Jack N; Waterman, Paige E; Lee, Christine; Hamer, Melinda J
Abstract: Background: Recent deadly outbreaks of Marburg virus underscore the need for an effective vaccine. A summary of the latest research is needed for this WHO priority pathogen. This systematic review aimed to determine progress towards a vaccine for Marburg virus. Methods: Article search criteria were developed to query PubMed for peer-reviewed articles from 1990 through 2019 on Marburg virus vaccine clinical trials in humans and pre-clinical studies in non-human primates (NHP). Abstracts were reviewed by two authors. Relevant articles were reviewed in full. Discrepancies were resolved by a third author. Data abstracted included year, author, title, vaccine construct, number of subjects, efficacy, and demographics. Assessment for risk of bias was performed using the Syrcle tool for animal studies, and the Cochrane Collaboration risk of bias tool for human studies. Results: 101 articles were identified; 27 were related to Marburg vaccines. After full text review, 21 articles were selected. 215 human subjects were in three phase 1 clinical trials, and 203 NHP in 18 studies. Vaccine constructs were DNA plasmids, recombinant vesicular stomatitis virus (VSV) vectors, adenovirus vectors, virus-like particles (VLP), among others. Two human phase 1 studies of DNA vaccines had 4 adverse effects requiring vaccine discontinuation among 128 participants and 31–80% immunogenicity. In NHP challenge studies, 100% survival was seen in 6 VSV vectored vaccines, 2 DNA vaccines, 2 VLP vaccines, and in 1 adenoviral vectored vaccine. Conclusion: In human trials, two Marburg DNA vaccines provided either low immunogenicity or a failure to elicit durable immunity. A variety of NHP candidate Marburg vaccines demonstrated favorable survival and immunogenicity parameters, to include VSV, VLP, and adenoviral vectored vaccines. Elevated binding antibodies appeared to be consistently associated with protection across the NHP challenge studies. Further human trials are needed to advance vaccines to limit the spread of this highly lethal virus.